THE INFLUENCE OF RETURN ON ASSETS, LEVERAGE, COMPANY SIZE, AND AUDIT COMMITTEE ON TAX AVOIDANCE - Silvianingrum, Helmy; Satyawan, Made Dudy (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to determine the effect of return on assets, leverage, company size, and audit committee on tax avoidance carried out by companies. The research method was quantitatively used, using a sample of 22 manufacturing companies from the consumer goods industry sector listed on the Indonesia Stock Exchange in 2020-2023. The data analysis technique used is multiple linear regression analysis through the SPSS application to measure the influence of each variable on tax avoidance. The results of this study indicate that return on assets has no significant impact on tax avoidance, while leverage, company size, and audit committee contribute significantly.